2000
DOI: 10.1046/j.1365-2435.2000.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought on the growth of Lolium perenne genotypes with and without fungal endophytes

Abstract: Summary 1.Grass leaves are often inhabited by fungal endophytes that can enhance host growth. In some forage species, endophytes improve host resistance to, and recovery from, drought. 2. Our objective was to determine if the growth of genotypes of Lolium perenne L. was improved by endophytes during recovery from drought. 3. Thirteen infected genotypes were cloned into ramets. Half were treated with a systemic fungicide to eliminate the endophyte (E-); half were untreated and retained high endophyte levels (E+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 51 publications
(129 reference statements)
3
124
1
Order By: Relevance
“…Metabolic costs for host plants harboring foliar endophytes have been implied to be the cause of negative impacts on plant performance and growth seen especially in natural ecosystems or under severe resource limitations (Cheplick et al, 1989(Cheplick et al, , 2000Faeth and Sullivan, 2003;Cheplick, 2004Cheplick, , 2007Faeth et al, 2004;Hesse et al, 2004;Faeth and Hamilton, 2006). In plants infected with mycorrhizal fungi the increased costs due to carbon flow to the fungus can be offset by increases in photosynthesis (Wright et al, 1998) and improved plant nutrition (Smith et al, 2001).…”
Section: Effects Of Endophyte Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic costs for host plants harboring foliar endophytes have been implied to be the cause of negative impacts on plant performance and growth seen especially in natural ecosystems or under severe resource limitations (Cheplick et al, 1989(Cheplick et al, , 2000Faeth and Sullivan, 2003;Cheplick, 2004Cheplick, , 2007Faeth et al, 2004;Hesse et al, 2004;Faeth and Hamilton, 2006). In plants infected with mycorrhizal fungi the increased costs due to carbon flow to the fungus can be offset by increases in photosynthesis (Wright et al, 1998) and improved plant nutrition (Smith et al, 2001).…”
Section: Effects Of Endophyte Infectionmentioning
confidence: 99%
“…Much less is known about the impacts of fungal endophytes on other plant performance parameters and metabolism, although endophyte infection has been implicated in increasing drought and mineral stress tolerance (Malinowski et al, 1998b;Malinowski and Belesky, 2000;Hesse et al, 2003Hesse et al, , 2005. However, the general mutualistic nature of this particular type of plant-fungus association has been disputed (Saikkonen et al, , 2007Mü ller and Krauss, 2005) and it was shown that positive effects of the endophyte on plant performance depend on genetic variation in the host and endophyte, and on nutrient availability (Cheplick et al, 1989(Cheplick et al, , 2000Cheplick, 2004Cheplick, , 2007Hesse et al, 2004). This link between resource availability and beneficial or neutral versus detrimental effects on plant performance suggests a metabolic cost of the endophyte to the host plant and recent publications indicate that metabolic effects of endophyte infection beyond the accumulation of alkaloids are of importance to the understanding of ecosystem wide impacts of this symbiosis (Hunt et al, 2005;Krauss et al, 2007;Rasmussen et al, 2007).…”
mentioning
confidence: 99%
“…They are diverse, ubiquitous, and can be isolated from flora worldwide, from flowerless plants such as mosses (Davey and Currah, 2006) to urban forest trees (Matsumura and Fukuda, 2013). These fungi can improve plant survival under adverse environmental conditions (Cheplick et al, 2000). Endophytes have been a focus of research as substitutes for agrochemicals (Rabha et al, 2014;Nath et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Typically growing intercellularly throughout above-ground plant tissue, fungal endophytes of grasses establish symbiotic relationships with their hosts ranging from parasitic and antagonistic to mutualistic [1]. In the mutualistic relationship, the host provides habitat and nutrients for the endophyte [1], while the fungus synthesizes anti-herbivore toxic alkaloids [3,4] and confers tolerance to stresses such as drought [5]. While most studies have focused on grass -endophyte and grass -herbivore interactions, direct effects of herbivores on endophytes have been ignored.…”
Section: Introductionmentioning
confidence: 99%